Seasonal cycle of circulation in the Antarctic Peninsula and the off-shelf transport of shelf waters into southern Drake Passage and Scotia Sea - Jiang, Mingshun; Charette, Matthew A.; Measures, Christopher I.; Zhu, Yiwu; Zhou, Meng (Deep Sea Research Part II: Topical Studies in Oceanography, 2013)
Author Posting. © The Author(s), 2013. This is the author's version of the work. It is posted here by permission of Elsevier B.V. for personal use, not for redistribution. The definitive version was published in Deep Sea Research Part II: Topical Studies in Oceanography 90 (2013): 15-30, doi:10.1016/j.dsr2.2013.02.029. The seasonal cycle of circulation and transport in the Antarctic Peninsula shelf region is investigated using a high-resolution (~2km) regional model based on the Regional Oceanic Modeling System (ROMS). The model also includes a naturally occurring tracer with a strong source over the shelf (radium isotope 228Ra, t1/2=5.8 year) to investigate the sediment Fe input and its transport. The model is spun up for three years using climatological boundary and surface forcing and then run for the 2004-2006 period using realistic forcing. Model results suggest a persistent and coherent circulation system throughout the year consisting of several major components that converge water masses from various sources toward Elephant Island. These currents are largely in geostrophic balance, driven by surface winds, topographic steering, and large-scale forcing. Strong off-shelf transport of the Fe-rich shelf waters takes place over the northeastern shelf/slope of Elephant Island, driven by a combination of topographic steering, extension of shelf currents, and strong horizontal mixing between the ACC and shelf waters. These results are generally consistent with recent and historical observational studies. Both the shelf circulation and off-shelf transport show a significant seasonality, mainly due to the seasonal changes of surface winds and large-scale circulation. Modeled and observed distributions of 228Ra suggest that a majority of Fe-rich upper layer waters exported off-shelf around Elephant Island are carried by the shelfbreak current and the Bransfield Strait Current from the shallow sills between Gerlache Strait and Livingston Island, and northern shelf of the South Shetland Islands, where strong winter ...